2008
DOI: 10.1038/nn.2108
|View full text |Cite
|
Sign up to set email alerts
|

Double dissociation of 'what' and 'where' processing in auditory cortex

Abstract: Studies of cortical connections or neuronal function in different cerebral areas support the hypothesis that parallel cortical processing streams, similar to those identified in visual cortex, may exist in the auditory system. However, this model has not yet been behaviorally tested. We used reversible cooling deactivation to investigate whether the individual regions in cat nonprimary auditory cortex that are responsible for processing the pattern of an acoustic stimulus or localizing a sound in space could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
215
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(230 citation statements)
references
References 48 publications
14
215
1
Order By: Relevance
“…When frequency‐matched injections were made into the MEG of the same animals, the resulting patterns of labeling demonstrate a tendency for the AAF to connect more strongly to the ADF and the A1 to the posterior fields. This distinct pattern of connectivity to other parts of the EG is consistent with the idea that the A1 and AAF comprise independent connectional systems, as proposed for cat auditory cortex (Lee et al, 2004), in which studies using cortical cooling have provided evidence for functional differences between the A1 and AAF (Malhotra and Lomber, 2007; Lomber and Malhotra, 2008). Detailed investigation of the cortico‐thalamic connectivity (ideally combined with gene expression studies such as in Storace et al, 2010) will provide further information about the potential differences in these processing streams.…”
Section: Discussionsupporting
confidence: 87%
“…When frequency‐matched injections were made into the MEG of the same animals, the resulting patterns of labeling demonstrate a tendency for the AAF to connect more strongly to the ADF and the A1 to the posterior fields. This distinct pattern of connectivity to other parts of the EG is consistent with the idea that the A1 and AAF comprise independent connectional systems, as proposed for cat auditory cortex (Lee et al, 2004), in which studies using cortical cooling have provided evidence for functional differences between the A1 and AAF (Malhotra and Lomber, 2007; Lomber and Malhotra, 2008). Detailed investigation of the cortico‐thalamic connectivity (ideally combined with gene expression studies such as in Storace et al, 2010) will provide further information about the potential differences in these processing streams.…”
Section: Discussionsupporting
confidence: 87%
“…The existence of separate hierarchical visual pathways for the analysis of object properties (the occipito-temporal "what" stream) and for the analysis of the spatial relationship between objects (the occipito-parietal "where" stream) is arguably one of the most influential theories about the organization of the visual system (9). Similarly, it was later postulated that auditory-cortical processing might follow such a dual principle of organization (23,24,27).…”
Section: Discussionmentioning
confidence: 99%
“…Lesion studies have indeed demonstrated the critical role of the auditory cortex for spatial hearing in humans (Duffour-Nikolov et al, 2012;Sanchez-Longo and Forster, 1958;Zatorre and Belin, 2001). Similar to the visual cortex dual-stream processing model, partially distinct ventral "what" and dorsal "where" auditory processing streams have been proposed for auditory processing (Barrett and Hall, 2006;Lomber and Malhotra, 2008;Rauschecker and Tian, 2000;Recanzone, 2000;Romanski et al, 1999;Tian et al, 2001;Warren and Griffiths, 2003). However, it remains poorly understood how the human brain implements the processing of auditory motion and location, and how these two processes differ from each other.…”
Section: Introductionmentioning
confidence: 98%